1982
DOI: 10.1104/pp.69.3.653
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Production of Digitalis Cardenolides by Plant Tissue Culture

Abstract: Shoot-Forming Cultures. The shoot-forming cafli of D. purpurea L., which had been established in the previous study (5), were transferred into the liquid basal medium, supplemented with 1 mg/L BA and 1 mg/L IAA, and cultured in the light. Thus, green, shoot-forming cultures without root were established and subcultured every 3 weeks. White, shoot-forming cultures were obtained by sub-culturing a portion of the green, shoot-forming cultures in the dark.Culture Condition. Murashige and Skoog medium (9)-with 1 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

1983
1983
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(21 citation statements)
references
References 7 publications
0
21
0
Order By: Relevance
“…In addition, the chloroplast-containing nonembryoid globules described in Sect. 2 as well as "undifferentiated" green cell cultures of D. purpurea formed only very small amounts of cardenolides ( [16] own unpublished results). Hence the morphological organization of the tissues is of higher importance for cardenolide formation and accumulation than the development of chloroplasts.…”
Section: The Influence Of Lightmentioning
confidence: 90%
See 2 more Smart Citations
“…In addition, the chloroplast-containing nonembryoid globules described in Sect. 2 as well as "undifferentiated" green cell cultures of D. purpurea formed only very small amounts of cardenolides ( [16] own unpublished results). Hence the morphological organization of the tissues is of higher importance for cardenolide formation and accumulation than the development of chloroplasts.…”
Section: The Influence Of Lightmentioning
confidence: 90%
“…Removal of BA from the medium and addition of gibberellic acid [16,17,32] or abscisic acid [17] also originated higher amounts of cardenolides in the cultures. In addition, growth and cardenolide content of the in-vitro cultivated shoots of D. lanata depended on the carbon and nitrogen sources, the phosphate level [17], as well as on the presence of inositol, thiamine, Mn2+, Zn 2 +, H3 B0 3, MoO~-, 1-, Fe 2 +, and EDTA in the medium (own unpublished results).…”
Section: Cardenolide Formation In Shoot Culturesmentioning
confidence: 93%
See 1 more Smart Citation
“…We have already reported that of the green shootforming cultures, white shoot-forming cultures, undifferentiated green cells and undifferentiated white cells of Digitalis purpurea L., the green shoot-forming cultures accumulated the largest amounts of digitoxin. 1) We next examined the effects of cultural conditions to determine the best for digitoxin formation by the green shoot-forming cultures. We have reported the effects of carbon and nitrogen sources, phosphate, vitamines, natural extracts and some plant growth substances previously,2) and we report here the effects of the other major and minor elements of the Murashige-Skoog basal medium used, the initial pH of the medium and precursors of the digitoxin biosynthesis.…”
mentioning
confidence: 99%
“…Multiple shoot cultures of Digitalis lanata (Hagimori et al 1982), D. purpurea (Lui & Staba 1979) and Catharanthus roseus (Hirata et al 1987) have been established for the production of digoxin, digitoxin and indole alkaloids, respectively. These cultures were maintained for long periods without changes in morphology, growth characteristics or in secondary metabolites production (Hirata et al 1990).…”
Section: Introductionmentioning
confidence: 99%